Thyrotropin Receptor Structure—In the Crystal New Horizons Shine - Furmaniak, Jadwiga; Sanders, Jane; Smith, Bernard Rees (Endocrine practice, 2009)
The thyrotropin receptor (TSHR) expressed on the surface of the thyrocytes plays a key role in thyroid physiology and is also an important autoantibody target in patients with thyroid autoimmunity. Just over 50 years ago in 1956, Adams and Purves made their milestone observation that the immunoglobulins from patients with Graves disease had the ability to stimulate the thyroid. Cloning of the TSHR complementary DNA sequence in 1989 was the next key development, which had considerable effect on studies of the TSHR. In particular, recombinant TSHRs could be expressed in different systems. The ability to produce recombinant TSHR enabled the development of animal antibodies to the TSHR that proved to be valuable tools for studying the structure and function of the receptor. After many years of efforts, the goal that was deemed by some as impossible was achieved when mouse and hamster thyroid-stimulating antibodies were produced.